Mineralized components and their interpretation in the histogenesis of peripheral ossifying fibroma - Devi Charan Shetty; Aadithya B Urs; Puneet Ahuja; Anshuta Sahu; Adesh Manchanda; Yuthicka Sirohi (Wolters Kluwer Medknow Publications, 2011)
Background: Peripheral ossifying fibroma (POF) is a lesion of gingival tissue that predominantly affects women and is usually located in maxilla, anterior to molars. The definitive diagnosis is established by histopathological examination, which reveals the presence of cellular connective tissue with focal calcifications. Objective: This study hypothesizes the histogenesis of POF by analyzing the diverse spectrum of mineralized components with a polarizing microscope. Materials and Methods: A retrospective study was undertaken which involved a detailed review of clinical, radiographic and histopathological features of 22 cases of POF, retrieved from departmental archives. These cases were subsequently stained with a histochemical stain (van Gieson) and observed under a polarizing microscope. Results: The study revealed that the most common age of occurrence was in second and third decades with a strong female predilection (73%), Interdental papilla of the maxillary anterior region was the most commonly afflicted site. About 90% cases showed no radiographic features.Histopathological examination showed that 73% cases consisted of a fibrocellular connective tissue stroma surrounding the mineralized masses. 50% mineralized masses comprised of woven bone, 18% showed combination of lamellar bone and cellular cementum, 18% showed only cementum (cellular and acellular), and remaining 13.6% exhibited a mixture of woven and lamellar bone under polarizing microscope. Conclusion: The study supports the theory that POF develops from cells of periodontal ligament (PDL)/periosteum as undifferentiated mesenchymal cells having an inherent proliferative potential to form bone or cementum, whose nature can be confirmed by polarizing microscope.